Influence of clays on fine particle filtration - Basnayaka, L.; Subasinghe, N.; Albijanic, Boris (Elsevier BV, 2018)
Filtration of fine particle slurries is known to be inefficient in most plant operations and the problem is exacerbated by the presence of even small quantities of clay minerals. This paper discusses the influence of the commonly encountered clay types, bentonite and kaolin, in the filtration of a pyritic gold ore and how the adverse effects can be mitigated by the addition of Ca2+ ions and a hydrophobic reagent respectively, depending on the clay type. The presence of both kaolin and bentonite clays resulted in increasing specific cake resistance, filter medium resistance and final cake moisture content while effects of bentonite clay being more detrimental. The addition of hydrophobic reagent DAH (dodecylamine hydrochloride) improved the filtration rate of kaolincontaining ore. The moisture content of the filter cake was also reduced. By contrast, in the case of the bentonitecontaining ore, the presence of DAH did not affect the filtration rate and the moisture content. Filtration of the bentonite-containing ore was significantly improved with the addition of Ca2+ ions.